Enfoque problémico en la enseñanza de ecuaciones diferenciales - Gualtero Martínez, Yuly Andrea; Rivera Vargas, Yuly Hadbleydy; Montes Jiménez, Carlos Mario (Revista Científica, 2011)
Speaks of the importance of the development of a model of teaching for mathematics methods class in the physic department of Pedagogical National University, based in the approach of daily problems for the students of this program, achieving the acquisition of relations between the differential equations and the naturals phenomeno.